PARTICLE RECYCLING IN VOLCANIC PLUMES - Veitch G.; Woods A.W. (My University, 2002)
We have developed a new theoretical model of an eruption column that accounts for the re-entrainment of particles as they fall out of the laterally spreading umbrella cloud. The model illustrates how the mass flux of particles in the plume may increase with height in the plume, by a factor as large as 2.5 because of this recycling. Three important consequences are that (1) the critical velocity required to generate a buoyant eruption column for a given mass flux increases, (2) the total height of rise of the column may decrease, and (3) we infer that in relatively wind-free environments, for eruption columns near the conditions for collapse, the recycling of particles may lead to an unsteady oscillating motion of the plume, which, in time, may lead to the formation of interleaved fall and flow deposits.